2016
DOI: 10.1177/2055217316680638
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies in relation to negative work events and accommodations in employed multiple sclerosis patients

Abstract: BackgroundJob loss is common in multiple sclerosis (MS) and is known to exert a negative effect on quality of life. The process leading up to job loss typically includes negative work events, productivity losses and a need for accommodations. By using active coping strategies job loss may be prevented or delayed.ObjectiveOur goal was to examine negative work events and accommodations in relation to coping strategies in employed relapsing–remitting MS patients.MethodsNinety-seven MS patients (77% females; 21–59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…On another note, though many countries have discrimination laws that are meant to protect patients against discriminating employment practices, covert and indirect encounters are still reported by MS patients within countries with these legislative structures. 29 , 30 , 32 In a hermeneutic phenomenology study conducted in Australia on why individuals with MS terminate their employment, Vickers discusses the concept of “Clayton’s choice”–“the choice you have when you do not really have a choice”. This study highlights the relational influences within a workplace and identifies that individual choices to leave work where accumulated negative experiences, such as being alienated, involuntary downgrading of duties, perceived negative attitudes or resentment from colleagues who were rostered to work more frequently as a consequence of their requested accommodation, prompt an “ugly passage out” or “being counseled out” by organizational members.…”
Section: Challenges and Determinants Of Employment In Ms Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…On another note, though many countries have discrimination laws that are meant to protect patients against discriminating employment practices, covert and indirect encounters are still reported by MS patients within countries with these legislative structures. 29 , 30 , 32 In a hermeneutic phenomenology study conducted in Australia on why individuals with MS terminate their employment, Vickers discusses the concept of “Clayton’s choice”–“the choice you have when you do not really have a choice”. This study highlights the relational influences within a workplace and identifies that individual choices to leave work where accumulated negative experiences, such as being alienated, involuntary downgrading of duties, perceived negative attitudes or resentment from colleagues who were rostered to work more frequently as a consequence of their requested accommodation, prompt an “ugly passage out” or “being counseled out” by organizational members.…”
Section: Challenges and Determinants Of Employment In Ms Patientsmentioning
confidence: 99%
“… 29 32 In a questionnaire-based study on the association between the encounter of negative work experiences and the use of various coping strategies, reports of negative events were associated with higher use of emotion-focused coping and absenteeism. 30 The researchers attribute the higher frequency of negative work events to individuals’ focus on managing the emotions that accompany the issue, rather than the work or task-related issue itself. 30 The study also assessed the levels of physical, psychological and cognitive functioning, but the researchers suggest that coping styles may be more influential in managing workplace dynamics and encounters, more so than self-reported cognition, physical abilities, fatigue and depression.…”
Section: Coping Styles and Strategies In Managing Msmentioning
confidence: 99%
See 2 more Smart Citations
“…15 To date, there are no studies in Argentina focused on coping styles adopted by PwMS and the influence these styles may have on health-related quality of life (HRQoL). There are several coping measurement instruments available, among which the "Ways of Coping Checklist", 16 "Coping with Health, Injuries and Problems Scale", 17 "Coping Inventory for Stressful Situations" 18 and "Coping Responses Inventory (CRI-A)" 8 instruments stand out. The only instruments validated in Argentina is the CRI-A and the Ways of Coping Checklist has been validated, but although the authors have not reported the procedure followed to carry out the adaptation.…”
Section: Introductionmentioning
confidence: 99%